Abusive supervision and moral disengagement: The role of ethical climate and team size - Martins, Sandra Isabel Conceição (2020)
Moral disengagement is a cognitive process related to ethics that allows individuals to perform unethical behaviors without a moral burden. This process and, in particular, the mechanism of displacement of responsibility, has been linked to leadership since the leader acts as a role model, influencing followers' behavior. Therefore, this study focuses on the influence of a specific type of leadership, abusive supervision, on followers' moral disengagement, with the mediation of instrumental ethical climate. Additionally, team size was introduced as a moderator due to the influence of group dynamics in organizational contexts. With a sample of 226 employees, results show that instrumental ethical climate fully mediates the positive relationship between abusive supervision and moral disengagement. Findings also highlight a conditional direct effect, being the relationship positive for teams sized up to seven members but negative when the team size is larger than 29 members. The results are discussed in terms of their implications for organizations.